Novice vs. Experienced Teachers: A Study of English Language Teaching Strategies - Luh Putu Artini; Ni Nyoman Padmadewi; Ni Made Ratminingsih; I Gede Yoga Permana (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2025)
The strategies employed by teachers in teaching English as a foreign language play a crucial role in determining students’ success in mastering the language. Prior research has consistently indicated that teachers’ instructional strategies are influenced by their learning experiences, formal education, and length of teaching experience. Studies in language pedagogy suggest that experienced teachers tend to demonstrate greater flexibility and pedagogical awareness in selecting and implementing teaching strategies, while novice teachers often rely more heavily on prescribed frameworks. Grounded in this literature, the present study aims to examine the differences in strategy selection and implementation between novice and experienced English teachers. This study adopted a mixed-methods approach involving self-rating questionnaires, classroom observations, and semi-structured interviews. The participants consisted of novice and experienced English teachers teaching at the secondary school level. Quantitative data from the questionnaires were supported and elaborated by qualitative data obtained from observations and interviews. The findings reveal both similarities and clear differences in the strategies used by novice and experienced teachers. Novice teachers tended to follow structured and predefined strategies aligned with their personal teaching standards, whereas experienced teachers demonstrated greater adaptability by modifying, combining, and contextualizing strategies to meet students’ needs and classroom dynamics. These findings highlight the importance of pedagogical flexibility in effective English language teaching. In conclusion, this study underscores the need for teacher education programs to emphasize reflective practice, differentiated strategy training, and mentorship to better prepare novice teachers for diverse instructional contexts.